The Effect of Precipitation on Scavenging of PM2.5 in Jakarta Based on Distributed Lag Non-Linear Models - Virgianto, Rista Hernandi; Kinanti, Nanda Putri; Ferdiansyah, Ervan; Kartika, Qurrata A’yun (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2021)
Fine particles, including PM2.5, impact human health, especially in a megacity such as Jakarta. Meanwhile, precipitation is one of the most efficient mechanisms to reduce atmospheric particulate matter, including PM2.5. This study investigated the changes in PM2.5 concentrations before and after rain events along with the threshold of precipitation and a certain time lag that affects the reduction of PM2.5 concentrations in Jakarta from 2017 to 2019. PM2.5 concentration datasets from two observation sites at Central and South Jakarta were used in this study. The relative effect and scavenging probability of PM2.5 concentrations were calculated to seek further understanding of the effect of rain events on the decrease of PM2.5 concentrations using hourly data. A Non-Linear Distributed Pause Model was used in this study with hourly rainfall data and hourly air temperature that controlled the reduction in PM2.5 concentrations. This study indicates that higher precipitation provides greater influence to the decrease of PM2.5 concentration in both Central Jakarta and South Jakarta. The precipitation threshold for reducing PM2.5 concentrations in Central Jakarta is 5 mm of rainfall with no time lag and a maximum delay of up to 12 hours. The South Jakarta area is 5 mm of rainfall with a time lag of up to 10 hours. In addition, the results suggest an increase in the probability of the concentration of PM2.5 below the standard (SP) with rainfall and a certain time lag that was greater in South Jakarta, which was up to 19% compared to 11% in Central Jakarta